The Performance of Jhumra as the Tharu Folk Ballad: A Study in Angst and Eco-Romance - Dagaura, Mohan (JODEM: Journal of Language and Literature, 2022)
This paper critically unravels the themes of Jhumra folk dance-songs of Dangaura Tharu of Nepal. On its interpretation, it discusses the imaginative representation of nature and human relationship in Jhumra songs appropriating the notions of the folklore performance of Richard Schechner and Alan Dundes. The paper appropriates Tharu Jhumra dance songs: Chhaila To, Jone Panah Gaili, Baigam Ture and Karam Lage Aag voiced by Mani Ram Tharu. The songs reflect the romantic fantasy and the suffering of the folks. Jhumra serves as the distinct dance repeatedly performed by the community throughout the year. Along with this, the brief reference of Robert Burns has also been fetched to spell out the modern revival and revisualization of folklores by the medium of YouTube and other commercial online platforms. Jhumra songs comprise the lyrics that romanticize and de-romanticize nature with the human–nature union. I have used Schechner's idea of performance as the way of life to signify the eco-centric romance of Tharu community. Schechner believes that performance is embedded in everydayness of each activity that a folk performs. This research will help to assimilate the eco-friendly nature of Tharu ethnicity and other different ethnicities of Nepal urging us to be more eco-conscious individuals.